2005
DOI: 10.1007/s10620-005-3046-2
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role of GLP-1 in the Pathophysiology of Early Dumping Syndrome

Abstract: Exaggerated plasma concentrations of GLP-1 precede reactive hypoglycemia after oral glucose in gastrectomy patients, resulting in late dumping syndrome. Recently, we showed that GLP-1 elicits the activation of sympathetic outflow. Because sympathetic activation is thought to be a cause of early dumping, we hypothesized that exaggerated GLP-1 may contribute to the pathophysiology of early dumping syndrome. In 11 patients after gastrectomy and 14 controls, blood pressure, heart rate, and plasma concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 28 publications
5
21
1
1
Order By: Relevance
“…In our study the median time from surgery to symptoms was 2.7 years, which is consistent with the time lag of 1-5 years that has been reported in case studies [5]. Dumping syndrome is seen after gastric bypass surgery [10,11]. Many patients with post-gastric bypass hypoglycaemia report dumping early after surgery [5] but this is controlled by dietary intervention, making it unlikely that dumping and post-gastric bypass hypoglycaemia are part of the same disease.…”
Section: Discussionsupporting
confidence: 89%
“…In our study the median time from surgery to symptoms was 2.7 years, which is consistent with the time lag of 1-5 years that has been reported in case studies [5]. Dumping syndrome is seen after gastric bypass surgery [10,11]. Many patients with post-gastric bypass hypoglycaemia report dumping early after surgery [5] but this is controlled by dietary intervention, making it unlikely that dumping and post-gastric bypass hypoglycaemia are part of the same disease.…”
Section: Discussionsupporting
confidence: 89%
“…Yamamoto et al reported the relation between GLP-1 and early dumping syndrome. They concluded that increasing catecholamine through the effect of GLP-1 on the central nervous system, which activates catecholamine neurons, might produce the symptoms of early dumping syndrome [23]. GLP-1 might confound postprandial hypotension and tachycardia by enhancing insulin-mediated vasodilatation through an increase in nitric oxide production [24,25].…”
Section: Fig 2 Continuous Glucose Monitoring (Cgm) Over 24 Hoursmentioning
confidence: 99%
“…However, following RYGB, increased (58) or unchanged (81) GIP levels have been reported in type 2 diabetic patients. On the other hand, GLP-1 has been implicated in the dumping syndrome and the reactive hypoglycemia that may follow gastric surgery (82). Its trophic actions on ␤-cells have been called upon to explain six cases of histologically proven nesidioblastosis after RYGB (83).…”
Section: Mechanismsmentioning
confidence: 99%